Effects of physical activity on subjective well-being: the mediating role of social support and self-efficacy - Guo, Siqiang; Fu, Huaying; Guo, Kelei (Frontiers in Sports and Active Living, 2024)
Objective: Subjective well-being is an essential component of college students' mental health, and the purpose of this study was to investigate the relationship between physical activity and subjective wellbeing among college students and to examine the mediating role of social support and self-efficacy between the physical activity and subjective well-being.This study utilized a cross-sectional design with a stratified whole group sample of 989 college students (Mage = 19.65 years, SD = 1.1) from three universities in Guangdong Province, China, and used the Physical Activity Scale, Subjective Well-Being Scale, Social Support Scale, and Self-Efficacy Scale for data collection. In this study, SPSS 26.0 was used for descriptive statistical analysis and correlation analysis of the collected data. Harman's one-way method was used to test for common method bias.(1) Physical activity, subjective well-being, social support and self-efficacy were significantly correlated with each other. Among them, physical activity was significantly and positively correlated with subjective well-being (r= 0.36), physical activity directly predicted subjective well-being (β = 0.125, t = 3.992, p < 0.01). ( 2) Physical activity positively predicted social support (β = 0.386, t = 12.505, p < 0.01) and self-efficacy (β = 0.358, t = 11.793, p < 0.01), social support significantly positively predicted subjective well-being (β = 0.332, t = 11.370, p < 0.01) and self-efficacy (β = 0.254, t = 8.744, p < 0.01), self-efficacy significantly and positively predicted subjective well-being (β = 0.255, t = 8.251, p < 0.01). (3) Not only did social support and self-efficacy play an independent mediating role between physical activity and subjective well-being, but social support and self-efficacy played a chain mediating role between physical activity and subjective well-being.This study enriched the theoretical guidance for physical activity in promoting college students' subjective well-being. In the practical teaching of promoting college students' subjective well-being, in addition to paying attention to stimulating physical activity, special attention should be paid to the promotion of social support and self-efficacy.